Persuasion knowledge toolkit: Requirements gathering with designer - Saidin, Aeni Zuhana; Macaulay, Catriona; Hine, Nick (2011)
Persuasion has played an important role in human life since it began.In the early 1990s a new approach called persuasive design was introduced into the HCI field.Persuasive design recognised that persuasion knowledge could be applied to the design and development of a variety interactive applications for changing people's attitudes and behaviours.However, the field remains very young, with the transfer of persuasion knowledge to interaction designers particularly limited.This paper presents work towards the design of a toolkit to make this knowledge more accessible to designers during the design lifecycle.The paper introduces our work towards a "Persuasion Knowledge Toolkit" (PToolkit).We present the key body of work undertaken so far; the generation of requirements for such a toolkit and our exploration of the challenges in making rich bodies of literature around topics such as persuasion accessible to designers.